2006
DOI: 10.1017/s0950268806006157
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Streptococcus pneumoniae, Haemophilus influenzae, Moraxella catarrhalis and Staphylococcus aureus isolated from the nasopharynx of healthy children attending day-care centres in the Czech Republic

Abstract: Nasopharyngeal carriage of potential pathogens was studied in 425 healthy 3- to 6-year-old children attending 16 day-care centres (DCCs) in nine Czech cities during the winter 2004-2005. The overall carriage of pathogens was 62.8% (Streptococcus pneumoniae, 38.1%; Haemophilus influenzae, 24.9%; Moraxella catarrhalis, 22.1%; Staphylococcus aureus, 16%). An age-related downward trend was observed for colonization with respiratory pathogens in contrast to Staph. aureus whose carriage was significantly higher amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
43
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 31 publications
10
43
3
Order By: Relevance
“…Pneumococcus was identified in 43% of children attending day care centres in Vilnius. This carriage rate was similar to that in geographically close regions: 44% in Estonia (13), 47% in St. Petersburg, Russia (14) and 38% in Czech Republic (15). Six serotypes (19F, 23F, 6B, 6A, 3 and 18C) from the 33 identified were predominant and comprised almost 60% of all isolates.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Pneumococcus was identified in 43% of children attending day care centres in Vilnius. This carriage rate was similar to that in geographically close regions: 44% in Estonia (13), 47% in St. Petersburg, Russia (14) and 38% in Czech Republic (15). Six serotypes (19F, 23F, 6B, 6A, 3 and 18C) from the 33 identified were predominant and comprised almost 60% of all isolates.…”
Section: Discussionsupporting
confidence: 78%
“…Six serotypes (19F, 23F, 6B, 6A, 3 and 18C) from the 33 identified were predominant and comprised almost 60% of all isolates. The prevalent serotypes represented a similar distribution in the neighbouring states (13)(14)(15).…”
Section: Discussionmentioning
confidence: 68%
“…A high carriage rate of S. pneumoniae, H. influenzae, S. aureus and M. catarrhalis was found, even though our study included children older than the populations usually studied. Previous European studies focusing on similar age groups found lower carriage rates [14,22]. Our data might be explained by the use of aspirates rather than swabs as sampling technique as well as enrichment broth for S. aureus recovery.…”
Section: Discussionmentioning
confidence: 40%
“…A negative association could occur when bacteria compete within same environment. Several studies have described a negative association between S. pneumoniae and S. aureus (12)(13)(14)(15)(16). Understanding of interactions between S. pneumoniae, H. infl uenzae, M. catarrhalis, and S. aureus is limited.…”
Section: Learning Objectivesmentioning
confidence: 99%